Benefit-cost analysis of increased funding for agricultural research and development in the global south - Rosegrant, Mark W.; Wong, Brad; Sulser, Timothy B.; Dubosse, Nancy; Lybbert, Travis J. (Cambridge University Press, 2023)
This paper conducts a benefit–cost analysis of expanding agricultural research and development (R&D) in the Global South. We extend a recent modeling exercise that used IFPRI’s IMPACT model to estimate the investments required to reduce the global prevalence of hunger below 5%. After 35 years, the increased funding is estimated to increase agricultural output by 10%, reduce the prevalence of hunger by 35%, reduce food prices by 16%, and increase per capita incomes by 4% relative to a counterfactual where funding continues to rise on historical trends. Using an 8% discount rate, the net present value of the costs of agricultural R&D are estimated at $61 billion for the next 35 years, while the net present benefits in terms of net economic surplus (the sum of consumer and producer surplus) are estimated at $2.1 trillion. The central estimate of the benefit–cost ratio (BCR) is 33, consistent with previous research documenting high average returns to agricultural research and development. The central BCR reported in this study places the intervention at the 91st percentile of all previous Copenhagen Consensus BCRs in agriculture, and 87th percentile for all BCRs regardless of sector. Agricultural R&D is likely one of the best uses of resources for the remainder of the Sustainable Development Goals and decades beyond.